Legal Regime of Smart Treaties in the Field of Foreign Economic Activity - Boltayeva Sh. B.; Kurbonova M. M.; Temirova R. Sh. (International Journal on Economics, Finance and Sustainable Development, 2021)
This article is about the legal regime of smart contracts in the field of foreign economic activity, the history of the origin of smart contracts and their current place. It also lists the advantages and disadvantages that arise in the process of putting smart contracts into practice. Smart contract is a computer algorithm designed to create, manage and present information about the ownership of something. In the narrow sense, a smart contract is a set of functions and data located at one address in a block chain.